The fourth form of reverse chain verticalization: a case study in the rubber sector - da Rosa Portella Tondolo, Rosana; Denicol Júnior, Sílvio; Honorato Schuch Santos, Carlos (Revista Gestão da Produção Operações e Sistemas, 2009)
Due to existing environmental concerns and the companies’ need to explore their competencies to the utmost so they become a competitive differential, there is reverse logistics. Reverse logistics is characterized by being a reverse movement in the supply chain, where products go through a reverse inverse path, that is, products go from final customers back to suppliers. In this context, this study aims at exploring a post- consumer reverse chain from a recycling service company perspective, in an attempt to rate the analyzed company’s performance. This is an exploratory study with a qualitative approach, in which a semi-structured questionnaire was used as technique for gathering data. This paper’s main results are: the classification of the company analyzed as a reverse logistics agent, identification of the fourth form of reverse chain verticalization, and the economic, financial and environmental benefits generated by this chain. Finally suggestions are made for future studies. Keywords: Reverse Chain; Reverse Logistics; Rubber Sector.